The Effect Of Summarizing Technique On Student’s Writing Ability - Rohdearni Sipayung; Lastiurma Gultom (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The significance of this research are expected to find out whether or not the students’ writing ability of the eight grade students of SMP N 10 Pematangsiantar can be improved through the Summarizing Technique. This research is pre - experimental that using a study group meanwhile collecting data of this research using pre-test and post - test design. There are two variables. Namely independent variable is Summarizing Technique and dependent is students’ writing ability. The population of this research was the students of the eight grade students of SMP N 10 Pematangsiantar which consist the number of students is 256 students. The writer will be doing research in class VIII -1 and VIII - 7 SMP N 10 Pematangsiantar. That students consist of 64 students in it. The instrument used in this research is writing text.The result of the mean score of the students pre-test was 59,43 and after giving the treatment the mean score of the students post - test was 71,59. The comparison between the mean scores in pre - test and post - test showed a difference and increased than before. The result of the t-test value is 15,2 was greater than t - table value 2000 with degree of freedom (df) N-1 (64 - 1). It means the teaching writing can improve the students’ writing ability of the eight grade students of SMP N 10 Pematangsiantar was accepted while null hypothesis (H0) summarizing Technique in teaching writing is able to improve the students’ writing ability of the eight grade students of SMP N 10 Pematangsiantar